Pluralism, Identity, and the State : National Education Policy Towards Indigenous Minorities in Japan and Canada - Takeda, N.; Williams, J. H. (2012)
This paper examines educational policies toward indigenous minorities in Japan and Canada during the period of nation-building, from the latter half of the nineteenth century to the first half of the twentieth century. Both Japan and Canada first segregated indigenous children into separate educational institutions and then tried to assimilate them into mainstream society. Beneath these broad policy similarities, however, lie different rationales, with substantially different implications for education and social policy in diverse societies. In Japan, national integration was promoted through a cultural or ethnic rationale, a socially coherent approach that nonetheless allows little room for minorities. Canada approached national integration using a notion of citizenship that both allows considerable space for minorities but is challenged by unity. These two strategies can be seen in two polar models of the state - a civic-assimilationist approach of the 'French model' and an ethnocultural exclusionist model of the formation of the German state. The paper argues for a multicultural pluralist model including both civic and cultural/ethnic identities.